Attitudes of Police Officers on the Implementation of Body Worn Cameras in the Police of Serbia - Milidragović, Dragan; Milić, Nenad; Stamenković, Miloš (NBP. Nauka, bezbednosti, policija, 2025)
Police organizations in the United States were among the first to implement body-worn cameras more than a decade ago. Shortly thereafter, law enforcement agencies across Europe also started to adopted body-worn cameras as part of their operational practices. These devices have been widely regarded as effective tools for addressing specific challenges in policing and improving overall police performance. In line with global trends in modernizing policing practices, the Serbian Police launched a pilot project for the implementation of body-worn cameras in September 2023. Prior to the initiation of this pilot phase, a research study was conducted to examine the attitudes and perceptions of police officers toward body-worn cameras. The findings of this study are intended to provide valuable insights for planning and decision-making related to the implementation process.
Keywords: body-worn cameras, police organizations, police reform, police accountability.